Giant unruptured aneurysm of the left coronary sinus of Valsalva presenting as acute coronary syndrome: a case report. Issue 2 (23rd April 2019) - Mørk, Sivagowry Rasalingam; Eftekhari, Ashkan; Tang, Mariann; Klaaborg, Kaj-Erik
Abstract: Background: Sinus of Valsalva aneurysm (SVA) is a rare cardiac anomaly that can be congenital or acquired. Unruptured aneurysms may be asymptomatic but can present as malignant arrhythmias, acute chest pain, and even sudden cardiac death. Both ruptured and unruptured SVAs may have fatal complications, thus prompt diagnosis and surgery is critical. Case summary: We report a successful surgical repair of an unruptured aneurysm of the left sinus of Valsalva presenting as acute coronary syndrome. Coronary angiography (CAG) and cardiac multislice computed tomography (CT) revealed a large unruptured aneurysm of the left sinus of Valsalva. Surgical repair was performed by resection of the aneurysm, aortic valve replacement with composite graft, and coronary artery bypass. Discussion: Aneurysm of the left sinus of Valsalva is an extremely rare condition. Correct diagnosis can be done by echocardiography, CAG, or CT. Non-ruptured aneurysms should be surgically repaired if they are associated with significant symptoms or if their size enlarge rapidly.